Revisiting Emergency Food Reserve Policy and Practice under Disaster and Extreme Climate Events - Jonatan A. Lassa; Paul Teng; Mely Caballero-Anthony; Maxim Shrestha (International Journal of Disaster Risk Science, 2018)
Abstract All food systems will continue to be affected by disasters and extreme climate events. Triggered by recent food crises around the world and climate change concerns, some governments have been trying to develop more robust and resilient food systems. One of the oldest options for many governments is to stockpile emergency food reserves for the purpose of food security and disaster preparedness. In the aftermath of the world food price crises in 2007–2008 and 2011, some governments in Asia have been maintaining emergency food reserves to ensure greater supply and price stability. Disasters and extreme climate events help governments to justify emergency food reserves. This research examined emergency food reserve policies in Indonesia, the Philippines, and Malaysia. Emergency food reserves emerged as a practice where the shared objectives of development, disaster risk reduction, and climate change adaptation have been demonstrated by governments. The findings suggest that most governments maintain the strong view that adequate emergency food reserves can buffer national food price shocks and shocks from disasters and climate change, and soften disruptions in trade due to export bans during times of disasters and climate emergencies.